Continuous Passive Mobilisation in the Hand - An Inexpensive Small Unit - G Alexander; H Garude; M R Thatte; N J Mokal (Indian Journal of Plastic Surgery)
An inexpensive device for continuous passive mobilization of the hand has been fabricated for usage in hand physiotherapy units. It is simple to use, effective and can be fabricated easily. 25 digits in 22 patients who suffered from a variety of hand injuries and consequent restricted joint motion were treated with this device. A high patient compliance, decreased pain and significant improvement in the range of motion were observed. The device is suitable for use in a hospital department. The concept and evolution of continuous pasive motion is also discussed.